Assessment of primary liver carcinomas other than hepatocellular carcinoma (HCC) with LI-RADS v2018: comparison of the LI-RADS target population to patients without LI-RADS-defined HCC risk factors. - Fraum, Tyler J.; Cannella, Roberto; Ludwig, Daniel R.; Tsai, Richard; Naeem, Muhammad; LeBlanc, Maverick; Salter, Amber; Tsung, Allan; Shetty, Anup S.; Borhani, Amir A.; Furlan, Alessandro; Fowler, Kathryn J. (European Radiology, 2020)
Objectives: To determine whether the LI-RADS imaging features of primary liver carcinomas (PLCs) other than hepatocellular carcinoma (non-HCC PLCs) differ between patients considered high risk (RF+) versus not high risk (RF-) for HCC and to compare rates of miscategorization as probable or definite HCC between the RF+ and RF- populations.Methods: This retrospective study included all pathology-proven non-HCC PLCs imaged with liver-protocol CT or MRI from 2007 to 2017 at two liver transplant centers. Patients were defined per LI-RADS v2018 criteria as RF+ or RF-. Two independent, blinded readers (R1, R2) categorized 265 lesions using LI-RADS v2018. Logistic regression was utilized to assess for differences in imaging feature frequencies between RF+ and RF- patients. Fisher's exact test was used to assess for differences in miscategorization rates.Results: Non-HCC PLCs were significantly more likely to exhibit nonrim arterial phase hyperenhancement (R1: OR = 2.94; R2: OR = 7.09) and nonperipheral "washout" (R1: OR = 3.65; R2: OR = 7.69) but significantly less likely to exhibit peripheral "washout" (R1: OR = 0.30; R2: OR = 0.10) and delayed central enhancement (R1: OR = 0.18; R2: OR = 0.25) in RF+ patients relative to RF- patients. Consequently, non-HCC PLCs were more often miscategorized as probable or definite HCC in RF+ versus RF- patients (R1: 23.3% vs. 3.6%, p < 0.001; R2: 11.0% vs. 2.6%, p = 0.009).Conclusions: Non-HCC PLCs are more likely to mimic HCCs on CT and MRI in the LI-RADS target population than in patients without LI-RADS-defined HCC risk factors.Key Points: • The presence of LI-RADS-defined risk factors for HCC tends to alter the imaging appearances of non-HCC PLCs, resulting in higher frequencies of major features and lower frequencies of LR-M features. • Non-HCC PLCs are more likely to be miscategorized as probable or definite HCC in the LI-RADS target population than in patients without LI-RADS-defined HCC risk factors.